2019
DOI: 10.1037/aap0000124
|View full text |Cite
|
Sign up to set email alerts
|

Internalized racial oppression as a moderator of the relationship between experiences of racial discrimination and mental distress among Asians and Pacific Islanders.

Abstract: This brief report examined the relationship of racial/ethnic discrimination and internalized racial oppression with mental distress in a sample of Asians and Pacific Islanders (APIs) in Alaska, where APIs compose the third largest racial group after Whites and Native Americans/Alaska Natives. Methods involved a cross-sectional, self-administered survey of 225 adult APIs in three Alaskan communities with large API populations. A subsample of the respondents who experienced racial/ethnic discrimination (n ϭ 123)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 43 publications
2
23
1
Order By: Relevance
“…In this regard, internalized racism seems to be consistently related to lower levels of personal and collective self‐esteem (e.g., Bailey, ; Clement, ; David & Okazaki, ; Utsey et al., ), psychological well‐being (e.g., Bailey, ; Ferrera, ), and life satisfaction (e.g., Bailey, ; David & Okazaki, ). Some studies have also found correlations between internalized racism and higher levels of hopelessness (Cort et al., ) and stress (e.g., Bailey, ; Garcia, David, & Mapaye, ; Grace, ; Szymanski & Obiri, ; Tull, Sheu, Butler, & Cornelious, ). There is also a growing body of empirical literature documenting internalized racism's links with specific psychological disorders like depression (e.g., Cajucom, ; David, , ; David & Okazaki, ; Molina & James, ; Mouzon & McLean, ; Utsey et al., ), anxiety (e.g., Clement, ; Graham, West, Martinez, & Roemer, ; Utsey et al., ), and body dissatisfaction (e.g., Cajucom, ; Cort et al., ; Mason, ).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, internalized racism seems to be consistently related to lower levels of personal and collective self‐esteem (e.g., Bailey, ; Clement, ; David & Okazaki, ; Utsey et al., ), psychological well‐being (e.g., Bailey, ; Ferrera, ), and life satisfaction (e.g., Bailey, ; David & Okazaki, ). Some studies have also found correlations between internalized racism and higher levels of hopelessness (Cort et al., ) and stress (e.g., Bailey, ; Garcia, David, & Mapaye, ; Grace, ; Szymanski & Obiri, ; Tull, Sheu, Butler, & Cornelious, ). There is also a growing body of empirical literature documenting internalized racism's links with specific psychological disorders like depression (e.g., Cajucom, ; David, , ; David & Okazaki, ; Molina & James, ; Mouzon & McLean, ; Utsey et al., ), anxiety (e.g., Clement, ; Graham, West, Martinez, & Roemer, ; Utsey et al., ), and body dissatisfaction (e.g., Cajucom, ; Cort et al., ; Mason, ).…”
Section: Resultsmentioning
confidence: 99%
“…Reverse causality is possible (i.e., negative physical and/or mental health state affecting discrimination and/or social support, or higher symptoms resulting from discrimination leading to seeking more social support). Additionally, other potential moderators were not explored, such as racial identity (e.g., Yip et al, 2019), coping styles (e.g., Brondolo et al, 2009), and internalized bias (e.g., Garcia et al, 2019). Participants were recruited only in English and primarily through the Internet and API- and/or SGM-related organizations, and participants included predominantly college-educated individuals of East Asian descent who identified as lesbian or gay.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of Filipino Americans, conceptualizing depressive symptoms through CM provided a culturally sensitive etiology of depression, indicating that the impact of historical oppression not only continues to impact mental health but also is a critical factor to consider in culturally inclusive conceptualization of mental health for ethnic minorities (David, 2008). A recent study with Asians and Pacific Islanders found that the relation between racial/ethnic discrimination and mental health was moderated by internalized inferiority (facet of CM) such that at higher levels of internalized inferiority, discrimination caused greater mental distress (Garcia et al, 2019). This finding is consistent with prior studies suggesting that covert forms of CM (i.e., internalized inferiority and cultural shame/embarrassment) are more likely to be related to mental health outcomes because of their stronger relationship to the internal self (David, 2010).…”
Section: CM Racism and Mental Healthmentioning
confidence: 99%